Rekonstruksi Peran Gender dalam Keluarga Dual Income: Antara Kesetaraan dan Realitas Domestik - Siti Nurul Azizah; Rani Rahmawati; Nisrina Salsabila (Pusat Studi Wanita dan Keluarga UGM, 2026)
Social changes marked by the increasing participation of women in the workforce have led to the emergence of dual-income families and influenced the dynamics of gender role division within households. This study aims to analyze the interpretation of the roles of husbands and wives, the process of role reconstruction in dual-income families, and the reality of domestic labor division amidst the discourse on gender equality. The method used is a descriptive qualitative approach with data collection techniques involving in-depth interviews with married couples who both work. Data analysis was conducted interactively through the stages of reduction, presentation, and drawing conclusions. The results of the study indicate that the interpretation of roles is still influenced by traditional values that position the husband as the primary breadwinner and the wife as the household manager, although flexibility is beginning to emerge through cooperation and mutual agreement. Role reconstruction occurs dynamically through processes of negotiation, communication, and situational adaptation in daily life. However, the division of domestic labor still exhibits inequality, with the wife continuing to bear the primary burden of household chores even though both partners work. This situation indicates that traditional gender norms and social constructs continue to strongly influence family practices. Therefore, there is a need to foster greater self-reflection, promote more equitable communication, and reinforce the value of gender equality to encourage a more equitable division of roles in dual-income families.